Stability analysis of rockfill and re-profiling method for slope rehabilitation [electronic resource] - Rahami Osman, author; Fakulti Kejuruteraan Awam (Skudai : Universiti Teknologi Malaysia, 2005)
Project Paper (Sarjana Muda Kejuruteraan Awam) - Universiti Teknologi Malaysia, 2005